On the Perils of Universal and Product-Led Thinking; Comment on "How Neoliberalism Is Shaping the Supply of Unhealthy Commodities and What This Means for NCD Prevention" - Clare Herrick (Kerman University of Medical Sciences, 2020)
Lencucha and Thow's paper offers an important addition and corrective to the burgeoning body of work in public health on the 'commercial determinants of health' in the context of non-communicable diseases (NCDs). Rather than tracing the origins of incoherence across policy sectors to the nefarious actions of industry, they argue that we need to be better attuned to the neoliberal ideologies that underpin these policies. In this commentary I explore two aspects of their argument that I find to be problematic: First, the suggestion that neoliberalism itself has some kind of deterministic or explanatory capacity across vastly different social, spatial, economic and political contexts. Second, I explore their concept of 'product-based NCD risk,' a perspective that disembodies and detaches risk from the social and structural conditions of their making.